Systematic Review: The Effect of the Enhanced Recovery After Surgery (ERAS) Protocol on Recovery, Pain Management, and Length of Hospital Stay in Cesarean Section Patients - Sri Mulyati; Aticeh Aticeh; Raudhatul Munawarah; Nur Fitri Ayu Pertiwi; Endah Endah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Cesarean section surgery often causes pain and prolongs hospital stays. The Enhanced Recovery After Surgery (ERAS) protocol offers a fast and comprehensive recovery solution. This systematic review aims to evaluate the effect of the ERAS protocol on recovery, pain management, and length of hospital stay in cesarean section patients. Researchers selected the literature using the PRISMA guidelines. The selection stages include identification, screening, eligibility assessment, and inclusion. literature articles retrieved from PubMed, Google Scholar, ScienceDirect, and the Cochrane Library. The researchers used specific keywords such as ‘ERAS protocol,’ ‘cesarean section’, ‘postoperative recovery’, ‘pain management’, and ‘length of stay’ to limit the search to articles published in the past five years (2021–2026). This process yielded five relevant articles for analysis. The review results show the ERAS protocol effectively accelerates physiological function recovery and physical mobility. ERAS also significantly reduces pain scores. Furthermore, patients experience a shorter length of hospital stay. This protocol demonstrates high safety and efficiency profiles. Healthcare facilities must implement ERAS as a standard of maternal nursing care to improve the quality of service for cesarean section patients.